2018
DOI: 10.1111/chd.12666
|View full text |Cite
|
Sign up to set email alerts
|

Complete atrioventricular canal repair with a decellularized porcine small intestinal submucosa patch

Abstract: Background Congenital heart defects affect nearly 1% of all children born per year in the United States, and complete atrioventricular canal (CAVC) accounts for 2%‐9%. While several patch materials have been used for septal defect closure during CAVC repair, clear superiority of one material over another has yet to be established. Methods A retrospective review of clinical outcomes following CAVC repair at Morgan Stanley Children’s Hospital/Columbia University was performed on operations conducted from March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A SIS-dECM patch, used to close ventricular and atrial septal defects in 73 paediatric CHD patients (average age 22 weeks) [117], showed lower rates of reoperations compared to other patch materials. Additionally, it exhibited more flexibility and ease of use.…”
Section: Xenografts For Chdmentioning
confidence: 91%
“…A SIS-dECM patch, used to close ventricular and atrial septal defects in 73 paediatric CHD patients (average age 22 weeks) [117], showed lower rates of reoperations compared to other patch materials. Additionally, it exhibited more flexibility and ease of use.…”
Section: Xenografts For Chdmentioning
confidence: 91%